2019
DOI: 10.5296/jad.v5i1.14421
|View full text |Cite
|
Sign up to set email alerts
|

Rebuilding Livelihood of the Rural and Peri-Urban Resettlers in Post-Involuntary Displacement of Saguling Dam Construction

Abstract: The construction of dams and reservoirs often comprises the displacement of not only communities but also the livelihood of the communities itself. This study aims to explore the effects of Saguling Dam construction on the livelihood re-establishment of the displaced people, by paying more attention on the sociographic localities of the new settlement, i.e. the rural and peri-urban areas. A survey was conducted on two groups of resettlers equiped with structured questionnaire. The results indicated that the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…As a result of excessive farming, the quality of the water deteriorated and fish production was greatly reduced (Sunardi et al, 2013). Sunardi et al (2019) investigated the lives of the resettlers using questionnaires and interviews in 2016 and 2018. The survey reported that 51 households relocated to the reservoir areas and 10 households relocated to peri-urban areas.…”
Section: Saguling Dam Indonesiamentioning
confidence: 99%
“…As a result of excessive farming, the quality of the water deteriorated and fish production was greatly reduced (Sunardi et al, 2013). Sunardi et al (2019) investigated the lives of the resettlers using questionnaires and interviews in 2016 and 2018. The survey reported that 51 households relocated to the reservoir areas and 10 households relocated to peri-urban areas.…”
Section: Saguling Dam Indonesiamentioning
confidence: 99%